Research on teaching and the education of teachers: Brokering the gap - Shavelson, Richard J. (BzL - Beiträge zur Lehrerinnen- und Lehrerbildung, 2020)
A few thousand years ago, Aristotle pointed out a gap between academic (research) knowledge and practical knowledge. The former is abstract, a generalization based on careful reasoning from evidence. The latter is specific, context-specific. Consequently, factors other than research knowledge come into play when teaching and when preparing teachers. A brief history of research on teaching highlights some of its rich contributions to the understanding of teaching. However, its contribution to educating teachers has, following Aristotle, limitations. Much more is involved in contextualized decisions about teaching action than research can address. Research knowledge is limited, for example, in its ability to inform teachers when and how to act in a situation. It is also limited in its ability to inform teachers as to how they should act considering the moral and ethical consequences of that action. Teachers need and use practical knowledge. Imparting that kind of knowledge is central to educating teachers. The job of teacher educators is to bridge the research-practice gap in preparing new teachers and enhancing capacity of practicing teachers. In a sense, teacher-educators are brokers in a trading zone between research and practice. Brokers should be recognized and trained in that role to advance the education of teachers. This said, preparing brokers fluent in teaching practice and scientific research has its challenges. These challenges include convincing the public and policymakers that more than scientific evidence is needed in preparing and supporting teachers, and convincing higher education institutions that doing so is legitimate and should be respected along with other professional programs such as medicine, law, business, and architecture.